Developing Computational thinking education though training among Chinese students - Zhang Yongheng; Zhang Feng; Liu Hongxia (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The 21st century is an era of ‘Computing Technology’ that has influenced every domain of human life. Such a high involvement and usage of Computing Technology have enhanced the need and requirement of computing education. There is a need to develop computational thinking skills of students aiming at students’ psychological and behavioral transformation favorably towards ‘Computing Technology’. The current research is carried out sampling 150 students from various universities in China. The objectives of this study include finding out how educational institutions and teachers can enhance the computational skills of students and what motivational strategies can significantly help students to undertake training programs and acquire advanced computational skills. This study also analyzes how to develop computing talent and computational thinking among university students. The study recommends that universities should make efforts to improve students' computational capabilities by taking training initiatives that would help students to improve their computational skills and prepare themselves for the need and demands of the world's job market.